Dendritic cell harmonised immunity to poultry pathogens; a review. Issue 3 (1st September 2017) - Rehman, Z.U.; Umar, S.; Meng, C.; Ullah, Z.; Riaz, F.; Rehman, S.U.; Ding, C.
Abstract : Dendritic cells (DCs) are antigen-presenting cells (APCs) with the unique ability to induce both innate immune responses and a highly specific acquired immunity. DCs are crucial to induce immunity, and their maturation and functions are influenced by microbial and environmental stimuli. Chicken DCs are composed of several subtypes including bursal secretory dendritic cells (BSDCs), follicular dendritic cells (FDCs), and thymic dendritic cells (TDCs). DC maturation depends on the nature of the perturbation and permits unique and efficient immune responses for each pathogen. DCs differentially recognise the viruses, bacteria, parasite and fungi and specifically regulate the immune response. Dendritic cells (DCs) are 'nature's adjuvants' and, as such represent an essential component of any vaccination strategy. The understanding of DC regulatory mechanisms opens a new horizon for the development of new vaccines and their targeting with the vaccination for elicitation of better immunity levels. The following review summarises the current state of knowledge of DCs and their specific functions during host pathogens interaction.